THE STABILITY OF SOCIAL RELATIONS IN THE SYSTEM OF CULTURE: FROM ANTIQUITY TO ENLIGHTENMENT - L. Filindash (Вестник университета)
The article is devoted to the study of culture as a system, represented in the aggregate of the items «manufacturer - artifact - user». Changes in the social relations of pairwise links within a structure are considered in a historical perspective from Antiquity through the Renaissance to the seventeenth century and the Enlightenment.